2019
DOI: 10.1103/physrevb.100.165402
|View full text |Cite
|
Sign up to set email alerts
|

Electronic transport in thin films of BaPbO3 : Unraveling two-dimensional quantum effects

Abstract: Recently, perovskite related BaPbO3 has attracted attention due to its hidden topological properties and, moreover, has been used as a thin layer in heterostructures to induce two-dimensional superconductivity. Here we investigate the normal state electronic transport properties of thin films of BaPbO3. Temperature and magnetic field dependent sheet resistances are strongly affected by two-dimensional quantum effects. Our analysis decodes the interplay of spin-orbit coupling, disorder, and electron-electron in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Figure 1 summarizes temperature-dependent MR data taken from a 15.0 nm thick BaPbO 3 thin lm showing an increase in MR to a maximum value at a magnetic eld of ≈ 0.85 T with a following decrease at higher magnetic elds, con rming our former results. [8] The MR data were corrected from concomitant EEI by subtracting its contribution via Equation (II.11) with = 0.906 retrieved from □ ( ) analysis. As expected, EEI contributes only slightly (see colored lines in Figure 1).…”
Section: B Experimental Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1 summarizes temperature-dependent MR data taken from a 15.0 nm thick BaPbO 3 thin lm showing an increase in MR to a maximum value at a magnetic eld of ≈ 0.85 T with a following decrease at higher magnetic elds, con rming our former results. [8] The MR data were corrected from concomitant EEI by subtracting its contribution via Equation (II.11) with = 0.906 retrieved from □ ( ) analysis. As expected, EEI contributes only slightly (see colored lines in Figure 1).…”
Section: B Experimental Results and Discussionmentioning
confidence: 99%
“…For consistency, we applied the just established self-consistent calculations of so and to the data presented in [8] comparing di erent sample thicknesses: For the sample with thickness 21.3 nm the WAL contribution expressed by so changes from 0.11 T to 0.127 T, whereas EEI represented by increases slightly from 0.97 to 0.974. The 4.8 nm thick sample shows a small increase of so from 0.24 T to 0.243 T, whereas changes from 0.84 to 0.887.…”
Section: B Experimental Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 shows temperature‐dependent MR data taken from a 15.0 nm‐thick BaPbO 3 thin film showing an increase in MR to a maximum value at a magnetic field of B 0.85 T with a following decrease at higher magnetic fields, confirming our former results. [ 8 ] The MR data were corrected from concomitant EEI by subtracting its contribution via Equation (11) with ζ = 0.91 retrieved from R ( T ) analysis. As expected, EEI contributes only slightly (see colored lines in Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we found that BaPbO 3 thin films grown on (001)‐oriented SrTiO 3 single crystals show single‐band behavior and a pronounced magnetoresistance (MR) which at low magnetic fields is evidently ruled by WAL. [ 8 ] Surprisingly, temperature‐dependent measurements of the sheet resistance R ( T ) account for an insulating low‐temperature state, contradicting the WAL result of magnetoconductance. Such a counterintuitive behavior of thin film samples was observed before.…”
Section: Magnetotransport In Single‐band Systems Governed By Disordermentioning
confidence: 99%